Strategies for disguise in written threatening communications and ransom demands: an analysis of English and German texts - Marko, Karoline (International Journal of Speech, Language and the Law, 2017)
Awarding Institution: Department of English Studies, Heinrichstraße 36, 8010 Graz, AustriaDate of Award: 17 January 2017